Seroprevalence of Free-Ranging Chicken Toxoplasmosis in Sub-Urban Regions of Shiraz, Iran - Jahan, M.S.; Asaduzzaman, M.; Sarkar, A.K. (International Journal of Poultry Science, 2006)
Toxoplasmosis is a widespread zoonotic disease that causes significant morbidity and mortality in the human fetus and in immunocompromised patients. Since the meat of chicken is considered one of the sources of the human infection, this study was undertaken to determine the prevalence of toxoplasmosis among free-ranging chickens (Gallus gallus domesticus). A total of 122 serum samples from chickens of four sub-urban properties of Shiraz city were collected and tested for toxoplasmosis by IFAT. The total prevalence of toxoplasmosis among chickens was 36.1%. The rate of seropositive chicken in titers of 1/16, 1/32, 1/64, 1/128, 1/256 and 1/512 was 20.5%, 5.74%, 5.74%, 3.28%, 0% and 0.82% respectively. The more prevalence of seropositivity was observed in Northern (56.7%) and Western (53.3%) regions. However, the prevalence in South (16.7%), and East (22.6%) of Shiraz city was low. Considering the high prevalence of toxoplasmosis in chickens, in the regions, control measures should be taken to prevent transmission of the infection to the animals and humans by Health and Veterinary organizations.